Stings on wings: Proteotranscriptomic and biochemical profiling of the lesser banded hornet (Vespa affinis) venom - Sunagar, Kartik; Khochare, Suyog; Jaglan, Anurag; Senthil, Samyuktha; Suranse, Vivek (Frontiers in Molecular Biosciences, 2022)
Distinct animal lineages have convergently recruited venoms as weaponry for prey capture, anti-predator defence, conspecific competition, or a combination thereof. Most studies, however, have been primarily confined to a narrow taxonomic breadth. The venoms of cone snails, snakes, spiders, and scorpions remain particularly well-investigated. Much less explored are the venoms of wasps (Order: Hymenoptera) that are infamous for causing excruciating and throbbing pain, justifying their apex position on Schmidt’s pain index, including some that are rated four on four. For example, the lesser banded wasp (Vespa affinis) is clinically important yet has only been the subject of a few studies, despite being commonly found across tropical and subtropical Asia. Stings from these wasps, especially from multiple individuals of a nest, often lead to clinically severe manifestations, including mastocytosis, myasthenia gravis, optic neuropathy, and life-threatening pathologies such as myocardial infarction and organ failure. However, their venom composition and activity remain unexplored in the Indian subcontinent. Here, we report the proteomic composition, transcriptomic profile, and biochemical and pharmacological activities of V. affinis venom from southern India. Our findings suggest that wasp venoms are rich in diverse toxins that facilitate antipredator defence. Biochemical and pharmacological assessments reveal that these toxins can exhibit significantly higher activities than their homologues in medically important snakes. Their ability to exert potent effects on diverse molecular targets makes them a treasure trove for discovering life-saving therapeutics. Fascinatingly, wasp venoms, being evolutionarily ancient, exhibit a greater degree of compositional and sequence conservation across very distant populations/species, which contrasts with the patterns of venom evolution observed in evolutionarily younger lineages, such as advanced snakes and cone snails.